Comprehensive Analysis of the Impact of Service and Product Quality on Purchasing Decisions through Purchase Intentions for Ice Cream Products - Prihatiningsih, Rahayu; Afronjiah, Afronjiah; Astuti, Ramlah Puji (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this study was to examine the influence of product and service quality on purchasing decisions, mediated by purchase intention as an intervening variable. The research was conducted to enhance purchasing decisions at Ice Cream Shop in Cirebon. Purposive sampling was used to select participants. The data were analysed using partial least squares structural equation modelling (SEM-PLS) with the Smart-PLS 3.0 application. The results indicate that service quality has a positive impact on purchase intention but does not significantly affect purchasing decisions. Additionally, the service quality variable affects purchase intention but does not significantly impact purchasing decisions. The study found that the purchase intention variable mediated the relationship between product quality and service quality on purchasing decisions. This study suggests that future researchers could investigate additional variables that may influence purchasing decisions at ice cream shops.